Specificity of V·O2MAX and the ventilatory threshold in free swimming and cycle ergometry: comparison between triathletes and swimmers - Roels, B.; Schmitt, L.; Libicz, S.; Bentley, D.; Richalet, J. P.; Millet, G. (British Journal of Sports Medicine, 2005)
Objectives: To compare maximal heart rate (HRMAX), maximal oxygen consumption (V·O2MAX), and the ventilatory threshold (VT; %V·O2MAX) during cycle ergometry and free swimming between swimmers and triathletes.